Development of State Green Sukuk as Part of Creative and Innovative Financing in the Islamic Financing Market - Yulitasari, Lis; Ekawati, Evi; Tresiana, Novita (KnE Social Sciences, 2024)
Along with the continued issue of green and sustainable development, fundraisers for finance project green is increasing. Principle investments in Islamic finance are combined with a draft-friendly environment and sustainability. The instrument of innovative Islamic finance-based continuity, like Green Sukuk in Indonesia, offers potential and importance for supporting the development economy in line with the effort for protecting the environment. This study aims to know the development of green sovereign Sukuk as part of creative and innovative financial market financing Islamic development. The method used by the author is qualitative, with a review of the literature. Literature research is a way to find relevant references to problems that arise. Research results show that the issuance of green Sukuk is an effort to apply sustainability in Indonesia. Green Sukuk is significant in Indonesia because this is one of the countries with a level of vulnerability and frequent disasters. Tragedy in growing hydrometeorology increases consequence changes, and increasing climate increases consequence development sustainability, which is not noticed in the environment. The continuous neglect of the environment has led to climate change causing droughts and floods which have a detrimental economic impact. Keywords: Green Sukuk, Islamic financial market, development financing